Needs Analysis for the Development of Project-Based Learning (PjBL) through an Android Application to Enhance Fiqh Learning Outcomes - Imas Masruroh; Tedi Priatna; Hapid Hapid; Tarsono Tarsono (CV. AFDIFAL MAJU BERKAH, 2025)
This study is motivated by the low learning outcomes of Madrasah Aliyah students in Fiqh, as preliminary research shows that only 70% of tenth-grade students met the minimum competency criteria (KKM) of 75, indicating suboptimal performance. The purpose of this study is to analyze the need for the development of Project-Based Learning (PjBL) through an Android application to improve Fiqh learning outcomes at MAN 2 Bandung and MAS Baitus Shofaa Ciheulang Ciparay Bandung. The research design employs a naturalistic qualitative approach. The sampling technique used is purposive sampling, and data collection methods include interviews, observations, and documentation. Data analysis is conducted using techniques of data reduction, data presentation, and verification.Research results revealed three key findings: 1) There is a need for more engaging, tech-based learning in Fiqh education, and the